221k views
0 votes
3(5j+2)=2(3j-6)(if there is no solution,type in ''no solution'')j= Answer

User Afreeland
by
5.6k points

2 Answers

1 vote

Answer:

j = -2

Explanation:

3 (5j + 2) = 2 (3j - 6)

15j + 6 = 6j - 12

15j - 6j = - 12 - 6

9j = - 18

j = - 18/9

j = - 2

User Jos Woolley
by
6.0k points
4 votes

Answer:

j = -2

Explanation:

It usually works well to start by eliminating parentheses.

15j +6 = 6j -12

Now you can subtract 6j from both sides to get the variable term on one side of the equation only:

9j +6 = -12

And you can subtract 6 from both sides to get the variable term by itself:

9j = -18

Now, dividing by the coefficient of the variable gives you the solution:

j = -2

The solution is j = -2.

User Matt Prelude
by
6.0k points